Evaluating EQ in Opium Addicts Visiting the Rehabilitation Centers of Rafsanjan University of Medical Sciences - Ali Asghar Ranjbar Totoei; Narges Khanjani; Mohammad Reza Mirzabeigi (Kerman University of Medical Sciences, 2016)
Evaluating EQ in Opium Addicts Visiting the Rehabilitation Centers of Rafsanjan University of Medical Sciences Ranjbar Totoei Aliasghar1, Khanjani Narges2*, Mirzabeigi MohammadReza3 Received: 19. 10. 2015             Revised: 16. 01. 2016              Accepted: 19. 02. 2016 1. MPH Student, Department of Epidemiology and Biostatistics, School of Public Health, Kerman University of Medical Sciences, Kerman, Iran. 2. Associate Professor, Department of Epidemiology and Biostatistics, School of Public Health, Kerman University of Medical Sciences, Kerman, Iran. 3. Assistant Professor of Psychology, School of Medicine, Rafsanjan University of Medical Sciences, Rafsanjan, Iran.    *Correspondence: Department of Epidemiology and Biostatistics, School of Public Health, Kerman University of Medical Sciences, Kerman, Iran. Tel: 034-31325102                                                                                     Email: n_khanjani@kmu.ac.ir Abstract: Introduction: EQ is one of the determinants of human reaction to life events. In this study, the EQ of addicts visiting the rehabilitation centers of Rafsanjan University of Medical Sciences in 2013 was evaluated. Method: This descriptive-analytical cross-sectional study was carried out on 122 addicts and 119 healthy people as controls. Addict subjects were chosen from the addicts visiting six rehabilitation centers of Rafsanjan Medical University. Participants were evaluated by BAR-ON questionnaire including 90 questions in four sub-categories of problem solving, emotional self- awareness, inter personal relationship and responsibility. Independent t-test and ANOVA wereused for analysis through SPSS19. Results: The two groups of addicts and controls showed significant differencein regard to EQ and the sub-categories of emotional self-awareness, interpersonal relationships and responsibility (P<0.001), but no difference in problem solving sub-category (P=0.074). Demographic variables such as age, gender, marital status or educational level did not affect EQ or its sub-categories. Conclusion: It can be assumed that higher EQ decreases the tendency toward addiction and the probability of addiction is less in people who have a higher emotional self-awareness, better interpersonal relations and accept more responsibility. Key words: EQ, Emotional intelligence, Opium addicts, Rafsanjan Citation: Ranjbar Totoei AA, Khanjani N, Mirzabeigi MR. Evaluating EQ in Opium Addicts Visiting the Rehabilitation Centers of Rafsanjan University of Medical Sciences. Journal of Health Based Research 2016; 1(3): 177-187.